Estimativa do potencial genotóxico do formocresol utilizado na prática odontológica - Ramos, Maria Emilia Santos Pereira (2004)
In odontology practice, many drugs used have different purposes, such as primary teeth pulp covers. The Formocresol is the medicine most used in pulpotomy of primary teeth in 1:5 dilution of Buckley’s formulation. The clinical safety of Formocresol has been questioned since its formulation is composed by formaldehyde, which is known as a toxic and carcinogenic compound. The present study has the objective of estimate the genotoxic potential of Formocresol in different dilutions using the commercialized sample. This study was evaluated by short period trials in vivo and in vitro. The animals were treated with Formocresol in the dilutions of 1:50, 1:100, 1:500 and 1:1000, and after 24h and 48h, they were sacrificed afterwards with the medulla extraction. This material was submitted to chromosomal damage observations (micronuclei) in polychromatic erythrocytes (PCE). The liver of the animals treated (24h group) were also submitted to histological analysis. In in vitro trial, the 1:750, 1:1000 and 1:2000 dilutions of Formocresol were incubated in human lymphocyte culture for 45 min and to comet test analysis next. There was no difference in micronuclei incidence evaluation when compared to 1:50, 1:100 and 1:500 dilutions and to negative control, in the 24h group. The difference appeared only when compared the 1:1000 dilution to the others, with a significant difference of p<0.001. However, when the dilution of 1:1000 was compared to the cyclophosphamide there was no significant difference (p>0.50). Meanwhile, the dilution of 1:1000 and of cyclophosphamide was statistically different from the negative control, in the 24h group. However, in the 48h group observations, only the cyclophosphamide presented micronuclei incidence, statistically differing from the treated groups and control (p<0.001). In the liver histological study it was observed hepatotoxicity in the animal treated in the 24h group. In comet analysis it was observed that in all used dilutions there was DNA crosslinks formation, which was an important factor to give a genotoxic potential to Formocresol. It was concluded that Formocresol is toxic and when diluted to 1:1000 is potentially genotoxic and mutagenic.